The Philippines yearbook, 2003 education. (Fookien Times Yearbook Pub., 2003)
This 2003 edition of the Philippines Yearbook discusses comprehensive insights into how education may be improved, starting with a detailed progress report from the Department of Education. The discussion starts at home parenting then, at school from elementary education and its teachers to high school education and its lifestyle, and finally the supporting non-government organization. Aside from the Education Theme, the yearbook also features the "EDSA odyssey from People Power to Paper Boats".